Hakikat Bahasa dan Budaya Melalui Tinjauan Tafsir al-Qur’an Surat al-Baqarah: 31-33, ar-Raḥmān: 1-4, dan Yūsuf: 2 - Hasan Syaiful Rizal (Universitas Yudharta Pasuruan, 2021)
Language has a very close relationship with human thought and culture. Some argue that the relationship of language with thought and culture is a subordinate relationship, i.e. language becomes part of human thought and culture. There are also those who argue that the relationship of language with human thought and culture is a coordinated relationship, i.e. language influences both, or vice versa that thought and culture influence language. Language and culture are two things that will be discussed in this study. Both will be studied through the views of experts on the interpretation and analysis of sura al-Baqarah verses 31-33, surah ar-Raḥmān verses 1-4, and surah Yūsuf verse 2, and various views of linguists. This research is literature research using content analysis techniques to formulate conclusions. The main data of this study is the literature of interpretation and linguistics. The conclusion of the data analysis is that language can be a deal and sometimes it is inspiring, and sometimes it is imitating the sounds of nature. While culture is the result of human thought that is very closely related to language. The relationship between culture and language can be sub-ordinative or coordinated.